Impacts of Chinese national centralized volume-based procurement policy targeting meropenem on prescription of designated antimicrobials for inpatients: an interrupted time series analysis - Lin, Zhi-Hang; Wang, Can-Ming; Cai, Li-Li (Frontiers in Pharmacology, 2025)
ObjectivesA national centralized volume-based procurement policy (NCVBPP) targeting meropenem has been implemented in China since December 2022. Here, the effects of the meropenem NCVBPP upon the prescription of designated antimicrobials for inpatients were explored.MethodsThe impacts of the meropenem NCVBPP on the consumption of and expenditures for designated antimicrobials prescribed for inpatients were evaluated by means of an interrupted time series analysis (ITSA) using both an autoregressive integrated moving average (ARIMA) model and a segmented regression model. The designated antimicrobials consisted of carbapenem-type antimicrobials and carbapenem-replaced antimicrobials; the latter referred specifically to combinations of penicillins/cephalosporins with beta-lactamase inhibitors and cephamycins. Data on the consumption of and expenditures for designated antimicrobials used in the inpatient sector of our hospital during the period ranging from January 2020 to March 2024 were collected and subjected to an ITSA.ResultsThe meropenem NCVBPP boosted the consumption of meropenem (generic drug and original counterpart); however, neither the total consumption of carbapenem-type antimicrobials nor that of carbapenem-replaced antimicrobials was affected by the meropenem NCVBPP. On the other hand, the meropenem NCVBPP significantly decreased the expenditures on meropenem. Its impacts on the total expenditures for carbapenem-type antimicrobials were unknown. Although a transient increase in the expenditures for carbapenem-replaced antimicrobials and a reduction in the overall expenditures for carbapenem-type antimicrobials plus carbapenem-replaced antimicrobials were also observed following the meropenem NCVBPP, these results were not necessarily caused by the meropenem NCVBPP.ConclusionThe meropenem NCVBPP triggers increased consumption of but reduced expenditures for meropenem. It has no effects on either the overall consumption of carbapenems or carbapenem-replaced antimicrobials.